The neurophysiological foundations of mental and motor imagery - Guillot, Aymeric; Collet, Christian (Oxford : Oxford University Press, 2010)
This text examines three main aspects of mental imagery. In the first part, the chapters address the neural basis of mental and motor imagery. The second part focuses on the evaluation of mental/motor imagery accuracy and the final chapters address the effects of mental practice on motor recovery after stroke.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Motor cortex; Perceptual-motor processes; Imagery (psychology); Movement disorders; Cerebrovascular disease; Neurophysiology